Annual report : West African clearing house - West African clearing house (Freetown : West African Clearing House, 1978)
This book highlights some of the basic functions of the West African clearing house in relation to its administrative annual report. The report examines various activities of the boards, in consonant to the financial statements of the registered central banks.
asm; 16/04/19
Ref
Keywords: Banks and banking; West African countries